Fyra generaliserade steg i lärandeprocessen: En vardagssociologisk betraktelse över gitarrspelande och sociologi (Sociologisk Forskning, 2022)
This essay was delivered as a speech by the outgoing president of the Swedish Sociological Association in connection with the bi-annual Sociologidagarna in Uppsala 16–18 March 2022. Guitar playing and sociology has many things in common, including how competence and skills are achieved. Based on everyday observations, four generalised stages in learning are outlined, that apply equally to guitar playing and sociology. To clearly differentiate each successive stage in the learning process, innovative analogies to bird life was used. In chronological order from novice to genius, the following separate stages of learning were identified: the birdhouse, the magpie, the lyrebird, and the nightingale. The birdhouse is characterised by surprise, confusion and almost total inability or ignorance, whereas the most prominent features of the magpie is curiosity, high energy and repetition. The lyrebird is occupied by imitation, self-centring and identity creation, whereas the nightingale shows clear signs of excellence and genuine innovation. Few guitar players and sociologists make the move from lyrebird to nightingale.
Keywords: sociologi; gitarrspelande; lärande; excellens